REPRESENTASI L’OREAL DALAM IKLAN BERBAHASA PERANCIS DAN INDONESIA (SUATU STUDI KOMPERATIF) - Alfadilah, Restu Nurul; Armin, Mardi Adi; Hasyim, Muhammad (JURNAL ILMU BUDAYA, 2017)
The title of this research is The Representation L'Oreal in the Advertising of the Language of the French and the Language of the Indonesian (a Coomparative Lesson) which examines the process of the sign and the representation of meaning in the Advertising of L'Oreal which is the Language of the French and the Language of the Indonesian. The purpose of the research is to explain how the trial of the sign in advertising L'Oreal which is the Language of the French and the Language of the Indonesian and to know the representation of the meaning that is in the advertising of L 'Oreal which is the Language of the French and the Language of the Indonesian being based on the trial of the sign. The theory that is used in this research is the theory of semiotics by Charles Sanders Peirce who deviating from the reference to identify the process of the sign and the theory of representation to explain the meaning of the sign that is found in the advertisement that is analyzed. The data that is used comes from the website. The type of advertising that is analyzed as sampo, revitalift and hair color. The result of the analysis of this research shows that the sign in the advertisement is based on icon, india and symbol and the transmission of meaning in advertising can be passed by the representation being based on the text, Image and color in advertising. Key words: advertising, representation, semiotic, beauty, productA. Latar BelakangDi zaman globalisasi ini media massa sudah menjadi kebutuhan dalam kehidupan sehari-hari, baik itu media cetak maupun media elektronik. Ini dikarenakan kebutuhan masyarakat yang selalu ingin memperoleh ataupun mengetahui informasi terbaru dari berbagai aspek kehidupan, salah satunya melalui media Iklan.Iklan merupakan salah satu media yang pada dasarnya mempromosikan suatu produk dengan menggunakan bahasa atau gambar sebagai unsur yang membangunnya. Dengan kata lain, iklan diciptakan melalui suatu cerita yang membawa pesan tertentu. Maka, dalam pembuatan sebuah iklan dimunculkan tokoh yang sentral melalui pemilihan model iklan yang menampilkan identitas tertentu. Selain pemilihan model iklan, penggunaan bahasa melalui tagline yang digunakan sangat memiliki peran penting dalam menarik perhatian para konsumen.Iklan juga harus menampilkan keunggulan dari